August Oxé, Howard Comfort, Philip Kenrick: Corpus vasorum Arretinorum. A Catalogue of the Signatures, Shapes and Chronology of Italian Sigillata. Second edition, 2000 - Horvat, Jana (Arheološki vestnik, 2002)
.